2010
DOI: 10.1002/pssb.201083966
|View full text |Cite
|
Sign up to set email alerts
|

Density change during the manufacturing process of PU–PE open cell auxetic foams

Abstract: This paper describes a modified manufacturing route involving a large change in density in auxetic negative Poisson's ratio (NPR) foams. Density change of auxetic foams after manufacturing is a common feature for this porous material. Samples of open cell PU-PE (i.e. the combination of polyurethane-polyethylene) foams with NPR are produced from two similar native materials using both the classical and the novel custom manufacturing methods. In the classical manufacturing route the cooling process is typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Bianchi et al have also recently presented a more classical example of auxetic fabrication resulting in large changes of the density of the auxetic foams. Manufacturing saw two batches of foam samples of varying dimensions placed into a metallic tube mould and compressed.…”
Section: Methods To Convert Conventional Foams Into Auxeticmentioning
confidence: 99%
See 1 more Smart Citation
“…Bianchi et al have also recently presented a more classical example of auxetic fabrication resulting in large changes of the density of the auxetic foams. Manufacturing saw two batches of foam samples of varying dimensions placed into a metallic tube mould and compressed.…”
Section: Methods To Convert Conventional Foams Into Auxeticmentioning
confidence: 99%
“…Numerous temperature–time combinations have been reported in the literature and are summarised in Fig. , where the heating time varied from 6 to 60 min but the majority of the time–temperature combinations were less than 20 min. The temperature applied varied between 130 and 220 °C , this wide range of temperatures can be explained considering the findings of Wang et al that foams with smaller cell size need higher heating temperatures and shorter processing times compared to foams with larger pore size.…”
Section: Parameters Affecting Manufacture Of Auxetic Foamsmentioning
confidence: 99%
“…Depending on whether negative values of Poisson ratio are observed in all crystallographic directions, in some of them or in none of them, one can define all materials as auxetics, partial auxetics and nonauxetics, respectively (). Recently, increasing interest in studies of auxetic materials and models was observed .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the variety of auxetic systems presented in the literature, manufacture of auxetic materials still remains a challenge. Several manufacturing routes have been proposed to convert a conventional (positive Poisson's ratio) foam into the auxetic one using heat treatment, thermo‐forming and compaction . The main approaches used for experimental manufacturing of auxetics are based on the rapid prototyping techniques such as the soft lithography , the selective electron beam melting , the digital micromirror device projection printing and the dip‐in direct laser writing .…”
Section: Introductionmentioning
confidence: 99%